2015
DOI: 10.1016/j.ultsonch.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl radical formation in batch and continuous flow ultrasonic systems

Abstract: The creation of free radicals by ultrasonic cavitation is the main mechanism that leads to chemical degradation of target pollutants and the process is considered an alternative advanced oxidation technology. The goal of this study was to compare the effects of batch and continuous flow ultrasonic systems on the formation of hydroxyl radicals. Ultrasonic batch experiments were conducted in two reactors (small and large) using a standard 20kHz catenoidal titanium horn at varying amplitudes and sonication times.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…The oscillating tip of the ultrasonic homogenizer resulted in a 90-times higher signal due to the high local energy input [36]. Converting the fluorescence signals to moles of hydroxyl radicals using the calibration curve, we found that 0.124 nmol/(L min) was generated by the microorifice, whereas the ultra-sonication sonotrode was capable of generating 11.25 nmol/(L min) which is in good agreement with expectations from the literature [37]. We expected that the same amount of hydroxyl radicals will result in similar levels of protein aggregation.…”
Section: Hydroxyl Radical Formation By Micro-orifice and Ultra-sonicasupporting
confidence: 86%
“…The oscillating tip of the ultrasonic homogenizer resulted in a 90-times higher signal due to the high local energy input [36]. Converting the fluorescence signals to moles of hydroxyl radicals using the calibration curve, we found that 0.124 nmol/(L min) was generated by the microorifice, whereas the ultra-sonication sonotrode was capable of generating 11.25 nmol/(L min) which is in good agreement with expectations from the literature [37]. We expected that the same amount of hydroxyl radicals will result in similar levels of protein aggregation.…”
Section: Hydroxyl Radical Formation By Micro-orifice and Ultra-sonicasupporting
confidence: 86%
“…There are also commercially available types of horns with a special geometry that are suitable for pipeline installation (e.g. radially vibrating donut horns) [32].…”
Section: Samplementioning
confidence: 99%
“…Several chemical reactions occur, like pyrolysis of water, oxidative species, reactive oxidative species and reactive nitrogen species reactions , . Degradation/changes of chemical molecules during ultrasonic processing could be related to oxidation reactions, promoted by the interaction of free radicals such as hydroxyl ( · OH) formed during sonication following the reaction (H 2 O → · OH + H · ) . An example is degradation of anthocyanins, chemical decomposition by opening of rings and formation of chalcone.…”
Section: Resultsmentioning
confidence: 99%
“…28,29 Degradation/changes of chemical molecules during ultrasonic processing could be related to oxidation reactions, promoted by the interaction of free radicals such as hydroxyl ( · OH) formed during sonication following the reaction (H 2 O → · OH + H · ). [30][31][32] An example is degradation of anthocyanins, 22 rings and formation of chalcone. Sonication results in a modification of macromolecular structures and a decrease of molecular weight.…”
Section: Quality Function Deploymentmentioning
confidence: 99%